An analytical approach to predict shear capacity of steel fiber reinforced concrete coupling beams with small span-depth ratio. (15th September 2018) - Zhao, Jun; Li, Kou; Shen, Fuqiang; Zhang, Xiangcheng; Si, Chenzhe
Highlights: The strut-and-tie model can be used in shear analysis of SFRC short coupling beams. The shear mechanism of short SFRC coupling beams was summarized to develop the model. The proposed model can reflect the effect of span-depth ratio on shear mechanism. The model considers the effect of steel fiber with different type and volume fraction. Abstract: Coupling beams with span-depth ratio no more than 2.5 tend to fail in shear-dominant rather than in flexure. The use of steel fiber in reinforced concrete coupling beams is considered as an available method to improve the shear strength and seismic behavior of coupling beams. This paper proposed a theoretical approach based on strut-and-tie model to predict the shear capacity of steel fiber reinforced concrete (SFRC) coupling beams with small span-depth ratio. To develop the model, the shear transfer mechanism was studied based on the test results of steel fiber reinforced concrete coupling beams with span-depth ratio no more than 2.5. The proposed model considered the effect of span-depth ratio, steel fiber with different type and volume fraction and concrete compressive strength on shear capacity. The shear predictions of the coupling beams were compared with the experimental values, and results indicated good accuracy of the proposed model.